Enhanced Technique For Maximizing Wireless Sensor Networks Lifetime Based On Utilizing The Phenomena Of Overlapping Nodes And Data Transmission - Al-Shalabi, Mohammed Abdel Lateif (2018)
Wireless Sensor Networks (WSNs) have attracted the attention of the researchers in the last few decades due to their involvement in many applications such as monitoring environment, fire tracking, and health care monitoring. In WSN, sensor nodes are deployed on the target area to sense the required events. The deployment of nodes can be formal (in specific locations) or random (in random locations). In the WSN that uses the random deployment of nodes, one of the common problems, when the sensors are close to each other, is the overlapping between them. This overlapping causes sensing approximately the same data by different nodes and also the transmission of duplicate data to the Cluster Head (CH), which leads to more energy consumption. Another problem in WSNs is the direct transmission of data from a CH to the Base Station (BS), which also negatively influences the overall network lifetime. Moreover, the random selection of the CHs leads to select nodes with low energy to be CHs which reduces the network lifetime. This thesis intends to solve the overlapping between nodes and the direct data transmission using different mechanisms. In this thesis, a mechanism is proposed to prolong the network lifetime by reducing the negative effect of the overlapping problem and utilizing the overlapping nodes to maximize the efficiency of the network in terms of network lifetime and energy consumption. This mechanism considers the distance between nodes in an efficient way in order to identify the overlapping between them based on the nature of the application with considering the blind area of the overlapping nodes.